DEVELOPMENT OF A RADIOPHARMACEUTICAL (PART II): FORMULATION, MARKING AND BIOLOGICAL DISTRIBUTION OF EC - López G., José (2001)
In Radiopharmacy the use of complexes as radiopharmaceutical requires that the procedure of labelling (complexing) achieves a radiochemical purity ot the complex ligand-Tc 99m greater than 98%. A study to find the chemical and physical parameters which allows the complexing of the EC ligand with Te 99m and the biological distribution is presented.